(untitled) (International Journal of Food and Nutritional Sciences, 2023)
The house sparrow (Passer domesticus) is a widely distributed bird species found throughout the world. Nests are the niche of bird which provide them shelter and support in reproduction. Nests are the structures constructed by the birds to lay their eggs, protect their offspring and also for the survival of the bird itself. Sparrow being a species, has close association with humans